Stability Analysis of Jet Fuel-Bioethanol Blends: an Experimental Approach - Chantika Putri Rahmawati; Shafa Putri Kamasinta; Kemal Putri Ginanjar; Lies Putri Aisyah; Riesta Putri Anggarani; Cahyo Setyo Wibowo; Nur Allif Fathurrahman (Scientific Contributions Oil and Gas, 2024)
Incorporating bioethanol into jet fuel blends has garnered increasing attention as a viable strategy to reduce dependence on fossil fuels and address environmental issues. This study investigates the influence of different amounts of bioethanol on the stability properties of jet fuel blends. Bioethanol addition to jet fuel causes a steady increase in its freezing point. The alteration has been attributed to the destabilizing effect caused by polar hydrogen bonds in bioethanol on the intermolecular forces. Oxidation stability analysis demonstrates a clear correlation between ethanol content and a swift decrease in pressure resistance. Although pure jet fuel is highly stable, mixes that include bioethanol show much lower stability. This decline highlights the reduced impact of bioethanol on fuel stability and oxidation processes. The simultaneous occurrence of gum formation emphasizes the need for careful formulation strategies to prevent stability problems and system complexities. Moreover, the complex influence of bioethanol on the temperature, stability, and oxidation properties of jet fuel blends highlights the importance of using accurate formulation methodologies to improve aviation fuels.